Three‐dimensional culture of oral progenitor cells: Effects on small extracellular vesicles production and proliferative function. (16th December 2019) - Yang, Yu; Knight, Rob; Stephens, Phil; Zhang, Ying
Abstract: Background: Small extracellular vesicles (SEVs) have a diameter between 30 and 150 nm and play a key role in cell‐cell communication. As cells cultured in 3D vs 2D behave differently, this project aimed to assess whether there were differences in SEVs derived from human oral mucosa lamina propria‐progenitor cells (OMLP‐PCs) cultured in a 3D matrix compared with traditional 2D monolayer cultures. Methods: OMLP‐PCs were cultured in 3D type I collagen matrices or on traditional 2D tissue culture plastic. Cell morphology and viability were assessed by light microscopy, actin staining, and trypan blue staining. SEVs secreted by OMLP‐PCs were purified and quantitatively analyzed by a BCA assay and nanoparticle tracking analysis (NTA; nanosight™). SEVs were further characterized by flow cytometry. SEV proliferative function was assessed by a 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay. Results: Cells cultured in 3D grew well as observed by light microscopy and phalloidin staining with cells branching in three dimensions (as opposed to the cells grown as monolayers on tissue culture plastic). NTA demonstrated a significantly higher number of SEV‐sized particles in the conditioned medium of cells grown in 3D type I collagen matrices vs a 2D monolayer ( P < .01). Like SEVs from 2D culture, SEVs from 3D culture demonstrated a particle size within the expected SEV range. Tetraspanin analysis confirmed that 3D‐derived SEVs were positive for typical, expected tetraspanins. Cell proliferation analysis demonstrated that SEVs produced through 3D cell culture conditions significantly reduced the proliferation of skin fibroblasts when compared with SEVs from 2D monolayers ( P < .05). Conclusion: 3D culture of OMLP‐PCs produced typical SEVs but in a greater amount than when the same cells were cultured in 2D. The downstream proliferative potential of the SEVs was influenced by the initial culture methodology. Future work should now assess the potential effects of 3D SEVs on key wound healing activities.